Gastro Retentive – Floating Drug Delivery System an Overview - Ramanathan, M; Subramanian, L; Manikandan, S; Venkatesan, N; P, Dr. Solairaj. (Asian Journal of Pharmaceutical Research and Development, 2017)
Drug efficacy, minimal frequency of administration and bioavailability are the major concern of every new drug development and formulation, the research is going on for existing drug novelty for above said. To achieve the novelty of formulation, researches applying various techniques to modify site specific drug release. The recent technological research has been focusing on site specific retardation of drug delivery system. Orally administered drug reaches to stomach, which plays an important fate of drug release for further process. Some narrow absorption window drug not able to release the medicament significantly in the specific part of stomach due course of time, thus leads to poor therapeutic effect. Drug bioavailability may impair due to lesser contact time with the specific stomach part. To overcome this problem several technical approaches are applied in formulation. Gastro retentive dosage forms (GRDFs) is one of the novel technique will facilitate the continuous prolong release of the drug at the upper part of gastro intestinal tract. This is significantly extend the duration of drug release thus enhance the bioavailability of narrow therapeutic absorption drugs. The prolongation of drug release reduce the frequency of dosing and better patient compliance. This review briefly discuss about various floating dosage of gastro retentive drug delivery system, advantages, disadvantages and limitation of floating system.